Best Answer

3m+4 = 6m-48

3m-6m = -48-4

-3m = -52

Divide both sides of the equation by -3 to find the value of m remembering that a - divided into a - is equal to a +:

m = 17 and 1/3

Or can just not devide both sides with -3 , cuz when you put -3 on the other side, you'll get -52 divided to 3 and get to the answer of -17.33(3)

:D Cheers !

More answers

To solve the equation 3m + 4 = 6m - 48, subtract 3m from both sides of the equation to get 4 = 3m - 48. Then, add 48 to both sides to get 52 = 3m. Finally, divide both sides by 3 to find the value of m, which is 17.

Q: What is 3m plus 4 equals 6m-48?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2m + 2 = 3m + 4 => 2m-3m = 4-2 => -m = 2 => m= -2

17

Well, 3m + m = 4m so 88 divided by 4= 22 there fore m =22 and 3m = 66

4 + 3m is already in its simplest form.

6m + 5 = 3m - 4Subtract 3m from each side:3m + 5 = -4Subtract 5 from each side:3m = -9Divide each side by 3:m = -3

Related questions

2m + 2 = 3m + 4 => 2m-3m = 4-2 => -m = 2 => m= -2

3m + 11n = 3

17

Well, 3m + m = 4m so 88 divided by 4= 22 there fore m =22 and 3m = 66

4 + 3m is already in its simplest form.

6m + 5 = 3m - 4Subtract 3m from each side:3m + 5 = -4Subtract 5 from each side:3m = -9Divide each side by 3:m = -3

6m + 20 = 9m - 4 24 = 3m m = 8

It is a linear equation in one variable, m. Although the question did not ask for a solution, here it is 3m + 23 = 6m - 4 Subtract 3m from both sides: 23 = 3m - 4 Add 4 to both sides: 27 = 3m Divide both sides by 3: 9 = m

It is: 4(2x+3m) when factorised

m=5

37m squared

It is a FALSE statement.